1973
DOI: 10.1007/bf01950378
|View full text |Cite
|
Sign up to set email alerts
|

Some experimental aspects of DSC determination of kinetic parameters in thermal decompositions of solids

Abstract: Some particular methods of collecting and treating DSC data for the determination of kinetic parameters in thermal decompositions of solids are suggested. These are mainly concerned with an extrapolation method to avoid the effect of the sample mass; with an approximate method to obtain the activation energy and the exponent of the decayqaw for runs at constant temperature in which the total area under the thermal curve is not known with accuracy; and with a method to ascertain whether a particular decompositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

1974
1974
1992
1992

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 5 publications
1
13
0
3
Order By: Relevance
“…Plots of u/time vs. time were made for the isothermal weight loss data (Figure 2) since this plot can give an indication of the type of mechanism of the decomposition (Guarini and Spinicci, 1972). Significantly, the shape of the curve is not consistent with an AvramiErofeev expression for the process, which requires a maximum in the c~/time vs. time curve, usually at a 0.6 or 0.7.…”
Section: Resultsmentioning
confidence: 99%
“…Plots of u/time vs. time were made for the isothermal weight loss data (Figure 2) since this plot can give an indication of the type of mechanism of the decomposition (Guarini and Spinicci, 1972). Significantly, the shape of the curve is not consistent with an AvramiErofeev expression for the process, which requires a maximum in the c~/time vs. time curve, usually at a 0.6 or 0.7.…”
Section: Resultsmentioning
confidence: 99%
“…( 1 972) and Guarini et al (1973) indicated that the decomposition was first-order in mass of NaHCO,. Since the reaction is not expected to be a surface phenomenon, this finding is logical.…”
Section: Calculation Of Rate Constantsmentioning
confidence: 98%
“…Also, rates of decomposition and of reaction with SO, have been measured separately on different samples (Subramanian et al, 1972; Guarini et al, 1973; Bares et al, 1970; Marecek et al, 1970).…”
Section: Scopementioning
confidence: 99%
See 1 more Smart Citation
“…The kinetic analysis of the thermal curves was performed as reported in previous papers [8,9]. From an examination of the Arrhenius plots of a number of laws usually applied to the kinetics of decomposition of solids [10], some evidence emerged:…”
Section: Calorimetric Measurementsmentioning
confidence: 99%